PEMANFATAAN MEDIA QUIZIZZ DALAM PROSES PEMBELAJARAN - Ali, Sabrina Salsabilla; Nikmah, Ainin; Khurin’ain, Khurin’ain; Kahfi, Muhammad Ray (Muta'allim: Jurnal Pendidikan Agama Islam, 2023)
The development of technology that exists today is growing. The existence of digital technology brings a new atmosphere to the world of education, especially in Indonesia. Learning becomes more interesting with the existence of technology-based learning media. One of the learning media based on digital technology is Quizizz. Quizizz is a digital platform for creating interactive quizzes with students that are very suitable for application in distance learning. Quizizz offers various interesting features for teachers to use with their students. The features offered include multiple choice quizzes, survey quizzes, essays, fill in the blank quizzes, checkbox quizzes, and so on. This research uses a qualitative approach and uses the literature review method by collecting data from journals and books related to the research topic as the main data source. The application of Quizizz in the learning process is a contemporary solution that adapts technology in learning so that students can learn interactively and not feel bored. In addition, this Quizizz application can also be used as a material for evaluating learning in class with the feature of calculating students statistics when working on evaluation questions. Abstrak Perkembangan teknologi yang ada pada masa kini kian berkembang. Adanya teknologi digital membawa suasana baru pada dunia pendidikan, khususnya di Indonesia. Pembelajaran menjadi semakin menarik dengan adanya media-media pembelajaran berbasis teknologi. Salah satu media pembelajaran yang berbasis teknologi digital ialah Quizizz. Quizizz merupakan sebuah platform digital untuk membuat kuis interaktif dengan peserta didik yang sangat cocok diaplikasikan dalam pembelajaran jarak jauh. Quizizz menawarkan berbagai fitur yang menarik untuk digunakan guru kepada siswanya. Adapun fitur yang ditawarkan diantaranya yaitu kuis pilihan ganda, kuis survey, esai, kuis mengisi bagian yang kosong, kuis mengisi kotak centang, dan lain sebagainya. Penelitian ini menggunakan pendekatan kualitatif dan memakai metode kajian pustaka dengan mengumpulkan data dari jurnal dan buku yang berhubungan dengan topik penelitian sebagai sumber data utama. Penerapan Quizizz dalam proses pembelajaran merupakan sebuah solusi masa kini yang mengadaptasi teknologi dalam pembelajaran agar siswa dapat belajar secara interaktif dan tidak merasa bosan. Selain itu, aplikasi Quizizz ini dapat dijadikan pula sebagai bahan evaluasi pembelajaran di kelas dengan fitur perhitungan statistik peserta didik saat mengerjakan evaluasi soal.